Influence of carbohydrate supplementation on skill performance during a soccer match simulation - Russell, M.; Benton, D.; Kingsley, M. (Journal of Science and Medicine in Sport, 2012)
Objectives This study investigated the influence of carbohydrate supplementation on skill performance throughout exercise that replicates soccer match-play. Design